2001
DOI: 10.1054/bjoc.2001.1774
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the prognostic impact of the Epstein–Barr virus-encoded latent membrane protein-1 expression in Hodgkin’s disease

Abstract: SummaryWe have examined expression of the Epstein-Barr virus (EBV) latent membrane protein-1 (LMP1) in the malignant Hodgkin and Reed-Sternberg (HRS) cells of Hodgkin's disease (HD) and its impact on response to treatment and on survival. Paraffin tissue from 100 adult immunocompetent patients with HD were analysed using immunohistochemistry to identify LMP1 expression. According to the Rye classification, 8% of patients had lymphocyte predominance (LP) subtype, 48% had nodular sclerosis (NS) disease, 37% were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
29
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 44 publications
8
29
0
1
Order By: Relevance
“…Glavina-Durdov et al 16 reported findings similar to those reported here in a 2-center study. This group found that HL tumor-cell EBV status had no impact on OS or disease-free survival (DFS) when their population was analyzed as a whole.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Glavina-Durdov et al 16 reported findings similar to those reported here in a 2-center study. This group found that HL tumor-cell EBV status had no impact on OS or disease-free survival (DFS) when their population was analyzed as a whole.…”
Section: Discussionsupporting
confidence: 89%
“…[1][2][3] The impact of the tumor-cell EBV status on the prognosis of patients with HL remains controversial. Most previous studies have not reported a significant association between EBV status and outcome, [4][5][6][7][8][9][10][11] while others have found that EBV-associated cases have either a more or less favorable prognosis [12][13][14][15][16][17][18] (Table 1). Some of the interstudy variation may be attributable to the different epidemiologic features of the disease in different geographic settings and some may be related to case selection.…”
Section: Introductionmentioning
confidence: 99%
“…LMP-1 can also upregulate expression of epidermal growth factor receptor (EGFR) (Miller et al, 1995), which may then modulate expression of specific STATs upon ligand stimulation (Petersen and Haldosen, 1998;Kloth et al, 2002;Leong et al, 2002). Interestingly, in line with our findings, despite the fact that LMP-1 of EBV is known for its transforming ability and promotes cellular proliferation in various studies (Baichwal and Sugden, 1988;Kaye et al, 1993), tumours with LMP-1 expression tend to have better prognosis in EBV-associated malignancies such as Hodgkin's disease (Montalban et al, 2000;Glavina-Durdov et al, 2001) and NPC (Hu et al, 1995). Regarding the intimate association between STATs and NPC, further clarification of the relation between STAT signalling and the gene expression pattern of EBV may shed light on the pathogenesis of this unique malignancy and might have future therapeutic applications.…”
Section: Discussionsupporting
confidence: 81%
“…The role of EBV status of HRS cells as an unfavorable prognostic marker is controversial (31)(32)(33)(34)(35) and probably limited to older adult patients. The association of EBV status with older age, a higher proportion of tumor-infiltrating CD68þ cells in EBER-positive HL, and higher levels of circulating EBV-DNA in older patients may all point to a different biology and disease activity in EBV-associated HL of the elderly, as factors contributing to unfavorable prognosis.…”
Section: Cd68mentioning
confidence: 99%